Natural trans-crotonin: the antiulcerogenic effect of another diterpene isolated from the bark of Croton cajucara Benth. - Hiruma-Lima, C. A.; Toma, W.; Gracioso, J. D.; de Almeida, ABA; Batista, L. M.; Magri, L.; de Paula, ACB; Soares, F. R.; Nunes, D. S.; Brito, ARMS (Pharmaceutical Soc Japan, 2002)
The nor-clerodane diterpene trans-crotonin isolated from the bark of Croton cajucara BENTH. was investigated for its ability to prevent the formation of gastric-mucosa ulceration in different experimental models in mice. The results obtained from crotonin were compared with those obtained with another diterpene, DHC (trans-dehydrocrotonin) in the same models. When previously administered (p.o.) at the dose of 100 mg/kg, crotonin, as well as DHC, significantly reduced (p<0.05) gastric injury induced by stress (72, 67%), indomethacin/bethanechol (78, 29%) and pylorus ligature (35, 30%). In the HCl/ethanol-induced gastric ulcer model, at oral doses of 100 and 250 mg/kg, crotonin significantly prevented (p<0.05) the formation of gastric lesions by 51 and 56%, respectively, when compared to the control group. Gastric injury was also of significantly less magnitude in the DHC treatment group (p<0.05). In the pylorus-ligature model, crotonin (p.o.), like cimetidine, increased the volume of gastric juice when compared to the control group (p<0.05). No significant modifications where found in gastric parameters such as pH or total acid content after oral crotonin treatment. However, systemic alterations were observed when crotonin (100 mg/kg) was previously administered intraduodenally to mice. We observed significant changes (p<0.001) in gastric-juice parameters such as an increase in volume and a decrease in gastric acidity. Those pre-treated with crotonin as well as with DHC did not increase free mucus production (p>0.05). The results suggest that crotonin presents a significant anti-ulcer effect when assessed in these ulcer-induced models. As with DHC, the antiulcerogenic effects of crotonin are probably related to anti-secretory or/and gastroprotective properties of this substance. In light of results obtained with DHC and natural trans-crotonin in the present study, we concluded that the A-ring of both diterpenes is not directly involved in the antiulcerogenic activity.
Keywords: crotonin DHC; gastroprotective activity; Croton cajucara; diterpene; Euphorbiaceae